If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) + -2 = 4x + 3 Reorder the terms: 5(1 + x) + -2 = 4x + 3 (1 * 5 + x * 5) + -2 = 4x + 3 (5 + 5x) + -2 = 4x + 3 Reorder the terms: 5 + -2 + 5x = 4x + 3 Combine like terms: 5 + -2 = 3 3 + 5x = 4x + 3 Reorder the terms: 3 + 5x = 3 + 4x Add '-3' to each side of the equation. 3 + -3 + 5x = 3 + -3 + 4x Combine like terms: 3 + -3 = 0 0 + 5x = 3 + -3 + 4x 5x = 3 + -3 + 4x Combine like terms: 3 + -3 = 0 5x = 0 + 4x 5x = 4x Solving 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 1x = 4x + -4x Combine like terms: 4x + -4x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| s^3-3s-2=0 | | 6(-3+-2x)(2+-1x)=0 | | 26+27=-39x-6 | | -5b-6-3b= | | 15-(4m+-5)=32 | | 10x-30=9x+11 | | 8+3x=0.5(16+6x) | | 5x-35=-5 | | 3=9+5y | | 3x-18=85 | | 5v^7=8 | | -l=n+5 | | 3(x+2)=4x+1 | | n/3-2=18 | | 13=48-x | | (kx^2)+(2k+1)x+1=0 | | 60=5m+5 | | 1x+10-7x= | | 5g+21=21 | | 13y-5y=56 | | 64+36=4x | | Y=0.5(4)2+46 | | 9/10g=9/10 | | 6x+18=-26+26+6x | | 2x+1=5-2(2x-1) | | 0.5a=9 | | 3h(4-3q)=520 | | 2p-1/4=2/3/4 | | 7y^4+28y^3+28y^2= | | 9-(2p+5)=4p | | 2x+16=8x+40 | | 18m=-360 |